COMMUNITY EMPOWERMENT TOWARDS WASTE UTILIZATION AS A MEANS OF PAYMENT FOR EDUCATION IN PALEMBANG CITY - Nofrima, Sanny; Janah, Salsanabilatul (TheJournalish: Social and Government, 2023)
The existence of economic problems in accessing formal education and the low awareness of the community of the importance of protecting the surrounding environment, so this study aims to explain how the perception of community empowerment towards the utilization of waste as a means of paying for education at Junjung Birru Kindergarten. Located on Jalan Demak 2 Ulu, Tuan Kentang Village, Jakabaring Sub-district, close to the slum area of Palembang City. The method used in this research is a qualitative approach using interview data collection techniques, data analysis, observation and recording. The source of data obtained was the results of interviews with the driver of Junjung Birru School Palembang City. The results showed that Junjung Birru School is a kindergarten school that focuses on increasing hygiene awareness in the community by implementing a waste payment system to help and reduce the burden on parents in paying monthly school fees. The school was established in 2007. The school was initially established because the founder of Junjung Birru School felt anxious and concerned about the amount of organic and non-organic waste that was carelessly thrown away in the community.